Active Learning on Center Stage: Theater as a Tool for Medical Education - Wendy L. Hobson; Krista Hoffmann-Longtin; Sana Loue; Linda M. Love; Howard Y. Liu; Christine M. Power; Susan M. Pollart (Association of American Medical Colleges, 2019)
Introduction Knowledge and skill development related to communication must incorporate both affective and behavioral components, which are often difficult to deliver in a learning activity. Using theater techniques and principles can provide medical educators with tools to teach communication concepts. Methods This 75-minute faculty development workshop presents a variety of techniques from theater and adapts them for use in medical education. Using examples related to diversity and inclusion, this session addresses general educational and theater principles, role-play, sociodrama, applied improvisation, and practical aspects of involving theater partners. The session materials include a PowerPoint presentation with facilitator notes, interactive activities to demonstrate each modality, and an evaluation. The sessions can be extended to longer formats as needed. Results Forty-five participants at Learn Serve Lead 2016: The AAMC Annual Meeting attended the 75-minute session. We emailed 32 participants 5 months after the conference, and eight responded. Participants reported that their confidence level in using theater techniques as a tool for medical education increased from low-to-medium confidence presession to high confidence postsession. All survey respondents who were actively teaching said they had made changes to their teaching based on the workshop. All commented that they appreciated the active learning in the session. Many indicated they would appreciate video or other follow-up resources. Discussion Principles and techniques from theater are effective tools to convey difficult-to-teach concepts related to communication. This workshop presents tools to implement activities in teaching these difficult concepts.